2013
DOI: 10.4236/jmmce.2013.16054
|View full text |Cite
|
Sign up to set email alerts
|

Strength Characterization of E-glass Fiber Reinforced Epoxy Composites with Filler Materials

Abstract: In this research work, an investigation was made on the mechanical properties of E-glass fiber reinforced epoxy composites filled by various filler materials. Composites filled with varying concentrations of fly ash, aluminum oxide (Al 2 O 3), magnesium hydroxide (Mg(OH) 2) and hematite powder were fabricated by standard method and the mechanical properties such as ultimate tensile strength, impact strength and hardness of the fabricated composites were studied. The test results show that composites filled by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 5 publications
1
48
0
Order By: Relevance
“…Devendra and Rangaswamy and Jena et al demonstrated that the impact energy values of GFRP composite increases with inclusion of filler is due to the improvement in bonding strength among inorganic filler, matrix and fiber. Thus ZnO filled GFRP composites has ability to absorb more energy, has greater fracture strength as compared to simple GFRP composite without filler and hence can stop crack propagation [35,36]. The behavior of impact test in present study depicts that ZnO will be promising filler in future composites.…”
Section: Izod Impact Testmentioning
confidence: 83%
See 1 more Smart Citation
“…Devendra and Rangaswamy and Jena et al demonstrated that the impact energy values of GFRP composite increases with inclusion of filler is due to the improvement in bonding strength among inorganic filler, matrix and fiber. Thus ZnO filled GFRP composites has ability to absorb more energy, has greater fracture strength as compared to simple GFRP composite without filler and hence can stop crack propagation [35,36]. The behavior of impact test in present study depicts that ZnO will be promising filler in future composites.…”
Section: Izod Impact Testmentioning
confidence: 83%
“…It is also due to increase in adhesion between matrix and reinforcements and reduced porosity due to addition of ZnO. As with increasing filler concentration in FRP composites, the inter particle distance is decreased which results in increased hardness [35,39].…”
Section: Hardnessmentioning
confidence: 94%
“…When ZnO NPs was loaded at 1 wt %, 5 wt %, and 10 wt %, the CTE value were reduced to 33.5 ppm/K, 31.3 ppm/K, and 30.1 ppm/K, respectively. Moreover, the TMA thermograms of the ZSQ showed no discernible transitions, which indicated that the nanosized ZnO NPs were well dispersed and the photocuring process complete . In addition, the nanoindentation results of UV‐cured LPMSQ, as well of ZnO composites, were summarized in Figure (B) As shown, both the modulus and hardness values drastically increased with increasing ZnO content.…”
Section: Resultsmentioning
confidence: 93%
“…Epoxy composites with high amounts of fillers have a smaller ability to absorb impact energy. The fillers disturb matrix continuity and each filler is a site of stress concentration which can act as a micro crack initiator and reduce the adhesion and energy absorption capacity of a composite [39,40] . In reference to spectroscopic results, it can be stated that the lack of chemical interaction between polymer and BMC filler leads to the presence of a weak interface region [41] .…”
Section: Charpy Impact Strength and Shore D Hardnessmentioning
confidence: 99%